One Year Clinical Evaluation of a Low Shrinkage Composite Compared with a Packable Composite Resin: A Randomized Clinical Trial - Razieh Hoseinifar; Elaheh Mortazavi-Lahijani; Hassan Mollahassani; Ahmad Ghaderi (Tehran University of Medical Sciences, 2017)
Objectives: The aim of this study was to evaluate the clinical performance of a packable and a low shrinkage methacrylate-based composite after one year. Materials and Methods:In this clinical trial, 50 class I or II restorations were placed in 25 patients. Each patient received two restorations. The tested materials were: (I) Filtek P60 + Single Bond 2 and (II) Kalore GC + Single Bond 2. The restorations were evaluated by two independent examiners after one week (baseline), six months and one year according to the modified United States Public Health Service (USPHS) criteria. The evaluated parameters included color match, marginal adaptation, anatomical form, retention, surface texture, postoperative sensitivity, marginal staining and secondary caries. Data were then analyzed using Friedman and conditional (matched) logistic regression tests at P<0.05 level of significance. Results: P60 and Kalore performed similarly at six months and one year (P>0.05). When each composite resin was evaluated independently at baseline and after one year, no statistically significant differences were found except for marginal adaptation (P60) where four restorations were rated Bravo (clinically acceptable). In 8% of restorations, patients expressed postoperative sensitivity. Conclusions: Kalore GC and Filtek P60 showed acceptance clinical performance after one year of service.